Sequencing, Expression, and Functional Analyses of Four Genes Related to Fatty Acid Biosynthesis During the Diapause Process in the Female Ladybird, Coccinella septempunctata L. - Xiang, Mei; Zhang, Hong-Zhi; Jing, Xiao-Yu; Wang, Meng-Qing; Mao, Jian-Jun; Li, Yu-Yan; Zang, Lian-Sheng; Zhang, Li-Sheng (Frontiers in Physiology, 2021)
The ladybird Coccinella septempunctata L. is a predatory insect that serves as an excellent natural biological control agent against common agricultural pests. C. septempunctata undergoes a significant diapause phenomenon, during which a large amount of fat accumulates in the abdomen. Comprehensive analysis of this lipid accumulation can reveal the detailed molecular mechanisms underlying diapause regulation, which can be exploited to improve the shipping and transport of this insect in agricultural applications. In this study, we compared the transcriptome of C. septempunctata during normal development, diapause, and post-diapause and screened four key genes related to lipid metabolism. The cDNA of these four relevant enzymes, acetyl-CoA carboxylase (ACC), long-chain fatty acid-CoA ligase (ACSL), elongase of very-long-chain fatty acids (ELO), and very-long-chain 3-oxoacyl-CoA reductase (KAR), were cloned using reverse transcription-polymerase chain reaction and rapid amplification of cDNA ends methods. Their expression profiles were analyzed during the preparation and maintenance of diapause and the post-diapause development phase. The functions of these four key enzymes in diapause were further verified using RNA interference. All four genes were most closely related to the homeotic gene from Tribolium castaneum. These four genes’ expression profiles were significantly affected under diapause-inducing conditions; the expression levels were the highest in early diapause and gradually decreased with the prolongation of diapause time. RNA interference showed that the target genes play important roles in fat storage during early diapause, and the decrease in their expression levels lead to a decrease in lipid content in C. septempunctata. These results indicate an important role of ACC, ACSL, ELO, and KAR in lipid accumulation, guiding further research to elucidate the mechanisms of diapause and improve biological control.